INFLUENCE OF DYNAMIC PROCESSES ON MORPHOLOGICAL CHANGE IN THE COASTAL AREA OF MEKONG RIVER MOUTH - Vinh, Vu Duy; Lan, Tran Dinh; Tu, Tran Anh; Anh, Nguyen Thi Kim; Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2016)
This paper presents some results on the influences of dynamic processes on morphological change in the Mekong river mouth area. The roles of these dynamic processes were assessed by the MORFAC (the morphological acceleration factor) method (Delft3D model) and analysis of 50 scenarios. Study results show that wave and river are dominant factors impacting on sediment transport and morphological change in the study area. In case of calm wave-wind, the interaction between river and tides creates deposition zones. Significant wave height in the range of 1 - 3 m is important factor that affects morphological changes in Mekong coastal area. The sediment accumulation in the flood season is the temporary distribution of sediments from the river. After flood season, sediments in the seabed are re-distributed and transported by the influences of dynamic processes in the condition of the lack of sediments. As a result, it creates the morphological change in the dry season.